Merchant Adventurer: The Story of W. R. Grace - James, Marquis (Rowman & Littlefield Publishers, 1993)
Marquis James's penchant for the sturdy individualists of our history, which has twice led him to a Pulitzer Prize, finds a sympathetic new subject in W. R. Grace, the Irish immigrant boy who not only opened new fields to American commerce but also became an outstanding mayor of New York and a powerful amateur in national politics. In this warm, nostalgic story, made possible by his access to the files of W. R. Grace & Co., James combines his gift for biography and his close acquaintance with business history to investigate a characteristic phenomenon of American life.